2008
DOI: 10.1002/jmri.21358
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted magnetic resonance imaging allows monitoring of anticancer treatment effects in patients with soft‐tissue sarcomas

Abstract: Purpose: To determine if diffusion-weighted imaging (DWI) can be used as a surrogate marker of tumor response to anticancer therapy in patients with soft-tissue sarcomas. Materials and Methods:Magnetic resonance imaging (MRI) including echo-planar DWI sequences was performed prospectively in 23 consecutive patients with soft-tissue sarcomas before and after initiation of regional or systemic chemotherapy. The mean interval between initial and follow-up MRI was 56.9 Ϯ 23.2 days. Tumor volumes were determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 22 publications
(26 reference statements)
4
93
1
2
Order By: Relevance
“…Several authors have shown the importance of DWI with ADC mapping to assess posttreatment response in osteosarcomas (14-16), but to our knowledge, few studies have reported its use in assessing response in soft-tissue sarcomas (17)(18)(19), although DWI has been used for detecting tumor recurrence and for characterizing soft-tissue tumors (19,27,31). Since changes at the cellular level are likely to occur before morphologic changes in tumor size occur, DWI is considered useful in detecting treatment response sooner than conventional imaging (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have shown the importance of DWI with ADC mapping to assess posttreatment response in osteosarcomas (14-16), but to our knowledge, few studies have reported its use in assessing response in soft-tissue sarcomas (17)(18)(19), although DWI has been used for detecting tumor recurrence and for characterizing soft-tissue tumors (19,27,31). Since changes at the cellular level are likely to occur before morphologic changes in tumor size occur, DWI is considered useful in detecting treatment response sooner than conventional imaging (18).…”
Section: Discussionmentioning
confidence: 99%
“…Since changes at the cellular level are likely to occur before morphologic changes in tumor size occur, DWI is considered useful in detecting treatment response sooner than conventional imaging (18). DWI changes have been shown to correlate…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor border was delineated manually, and the area was automatically calculated by using ImageJ. Given the irregular contour and shape of the tumors, the tumor volume V was calculated according to the following equation: V = s · (a 1 + a 2 + a 3 + ... + a n ), where s is the section interval and a 1 through a n are the areas of sections (21). Relative tumor volume (RTV) at different time points …”
Section: In Vivo Experiments In Pigsmentioning
confidence: 99%
“…DW imaging was performed in coronal or axial orientation by employing a spin echo echoplanar imaging (17). This resulted in significant signal attenuation of vessels, which is called black-blood image (18).…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%